Stabilization of the vertical instability by non-axisymmetric coils. (5th July 2016) - Turnbull, A.D.; Reiman, A.H.; Lao, L.L.; Cooper, W.A.; Ferraro, N.M.; Buttery, R.J.
Abstract: In a published Physical Review Letter (Reiman 2007 Phys. Rev. Lett .99 135007), it was shown that axisymmetric (or vertical) stability can be improved by placing a set of parallelogram coils above and below the plasma oriented at an angle to the constant toroidal planes. The physics of this stabilization can be understood as providing an effective additional positive stability index. The original work was based on a simplified model of a straight tokamak and is not straightforwardly applicable to a finite aspect ratio, strongly shaped plasma such as in DIII-D. Numerical calculations were performed in a real DIII-D -like configuration to provide a proof of principal that 3-D fields can, in fact raise the elongation limits as predicted. A four field period trapezioid-shaped coil set was developed in toroidal geometry and 3D equilibria were computed using trapezium coil currents of 10   k A, 100   k A, and 500   k A . The ideal magnetohydrodynamics growth rates were computed as a function of the conformal wall position for the n   =   0 symmetry-preserving family. The results show an insignificant relative improvement in the stabilizing wall location for the two lower coil current cases, of the order of 10 −3 and less. In contrast, the marginal wall position is increased by 7% as the coil current is increased to 500   k A, confirming the main prediction from the original study in a real geometry case. In DIII-D the shift in marginal wall position of 7% would correspond to being able to move the existing wall outward by 5 to 10 cm. While the predicted effect on the axisymmetric stability is real, it appears to require higher coil currents than could be provided in an upgrade to existing facilities. Additional optimization over the pitch of the coils, the number of field periods and the coil positions, as well as plasma parameters, such as the internal inductivity ℓ i, β, and q 95 would mitigate this but seem unlikely to change the conclusion.